A novel lumped‐parameter model of crosstalk between vias in high‐speed PCBS. Issue 9 (27th June 2016) - Cheng, Weichang; Xu, Shen; Yu, Juzheng; Sun, Weifeng
ABSTRACT: The method for lumped‐parameter via crosstalk (LPVC) model development is proposed in this letter. Good agreement between the full‐wave modeling and the physics‐based via simulation has been achieved in frequency‐domain. This model is easier to construct and allows researchers to better understand the impact of each parameter on crosstalk between via than former models. Analysis results show that, both power/ground (P/G) geometry and via distance have significant influences on crosstalk between vias on high‐speed printed circuit board (PCB). © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2088–2090, 2016